Providers, Unmarried Young Women, and Post‐Abortion Care in Kenya. Issue 4 (22nd September 2017) - Izugbara, Chimaraoke O.; Egesa, Carolyne P.; Kabiru, Caroline W.; Sidze, Estelle M.
Abstract: Young women and girls in Kenya face challenges in access to abortion care services. Using in‐depth and focus group interviews, we explored providers' constructions of these challenges. In general, providers considered abortion to be commonplace in Kenya; reported being regularly approached to offer abortion‐related care and services; and articulated the structural, contextual, and personal challenges they faced in serving young post‐abortion care (PAC) patients. They also considered induced abortion among young unmarried girls to be especially objectionable; stressed premarital fertility and out‐of‐union sexual activity among unmarried young girls as transgressive of respectable femininity and proper adolescence; blamed young women and girls for the challenges they reported in obtaining PAC services; and linked these challenges to young women's efforts to conceal their failures related to gender and adolescence, exemplified by pre‐marital pregnancy and abortion. This study shows how providers' distinctive emphasis that young abortion care‐seekers are to blame for their own difficulties in accessing PAC may add to the ongoing crisis of post‐abortion care for young women and adolescent girls in Kenya.